Genome degradation in plant tissue culture - Matthew W. Davis; Charles A. Leslie; Chaehee Lee; Evan Long; Li Meinhold; Megan Lorenc; Franklin Lewis; Patrick J. Brown; Grey Monroe (Proceedings of the National Academy of Sciences, 2026)
Many plants, unlike most animals, can reproduce as clones [D. Kester, HortScience 18 , 831–837 (1983), 10.21273/hortsci.18.6.831]. Cloning plants is vital to agriculture and biotechnology [H. Barton, T. Denham, Quatern. Int. 489 , 17–25 (2018), O. L. Gamborg, In Vitro Cell. Dev. Biol. Plant 38 , 84–92 (2002), K.-H. Neumann, A. Kumar, J. Imani, Plant Cell and Tissue Culture—A Tool in Biotechnology: Basics and Application (ed. 2, 2020)], but the extent to which somatic mutation arises during asexual propagation remains an outstanding question. Leveraging a natural experiment of walnut clones spanning five decades and multiple cloning methods, we found a complex history of somatic mutation revealing developmental cell dynamics. A haplotype-phased reference genome exposed extreme genomic instability, a distinct mutation spectrum, and a >3,500% increase in mutation rate within clonal somatic embryos. Pairing these mutations with the haplotype-phased assembly revealed the canonical flowering plant meristematic layers from bulk tissue sequencing and uncovered frequent fixation events throughout development. These findings raise concerns about genomic integrity in tissue culture, test assumptions about mutagenesis in clonal propagation, and establish a benchmark for emerging paradigms in somatic mutation research.